2019
DOI: 10.1016/j.celrep.2019.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into DNA-Dependent Activation of Human Metalloprotease Spartan

Abstract: Highlights d The crystal structure of human Spartan bound to DNA is determined d The SprT domain contains a Zn 2+-binding subdomain that binds single-stranded DNA d DNA engages two Spartan molecules with a conserved dimer interface in the crystal d DNA positions the SprT domain for optimal cleavage of DNAprotein crosslinks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 52 publications
4
51
0
Order By: Relevance
“…Our data suggest that the p97-TEX264 complex enables TOP1cc proteolysis by SPRTN. This conclusion is supported by a recent strutural analysis of SPRTN's active site 61 . The catalytic core of SPRTN is located within a narrow groove that is only accessible to small, flexible peptides, such as the disordered tails of histones.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our data suggest that the p97-TEX264 complex enables TOP1cc proteolysis by SPRTN. This conclusion is supported by a recent strutural analysis of SPRTN's active site 61 . The catalytic core of SPRTN is located within a narrow groove that is only accessible to small, flexible peptides, such as the disordered tails of histones.…”
Section: Discussionsupporting
confidence: 57%
“…A recent structural study demonstrated that the protease active site of SPRTN is located within a narrow groove that is only accessible to flexible peptide structures and not globular proteins HA S1 X X Denature: SDS/95 °C TEX264 TEX264-associated proteins TEX264 S1 + ARTICLE such as TOP1 61 . Therefore, large DPCs, such as TOP1ccs, likely need to undergo remodelling before their cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…ArdC is structurally similar to DNA-binding dependent metalloproteases involved in the maintenance of genetic stability such as Spartan or IrrE. Human Spartan protein cleaves DNA-protein crosslinks [15] meanwhile IrrE plays a central regulatory role in DNA protection and repair pathways in response to radiation [16]. ArdC structure differs from other known plasmidcoded antirestriction proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The closest structural homologues were the DNA binding metalloproteases Spartan (PDB: 6MDW; Z-score: 6.4) and IrrE (PDB: 3DTE; Zscore: 5.5). Spartan is a protein involved in the cleavage of proteins irreversibly crosslinked to DNA to preserve this way genome stability [15]. IrrE protects D. radiodurans from UV radiation DNA damage by proteolysis of a transcriptional regulator, DdrO, involved in SOS response [16].…”
Section: Ardc Is Needed In Recipient Cellsmentioning
confidence: 99%
“…Furthermore, the protease activity of SPRTN is tightly regulated with a switch that depends on its DNA binding, ubiquitination, and autocleavage [14][15][16][17][18]. Both single-and double-stranded DNA can activate the protease activity of SPRTN, with single-stranded DNA being more effective [14][15][16]107]. SPRTN can be monoubiquitinated, but only unmodified SPRTN binds to chromatin [15].…”
Section: Proteolysis-dependent Repair Mechanisms Targeting Cross-linkmentioning
confidence: 99%